2019
DOI: 10.1136/vetreco-2017-000239
|View full text |Cite
|
Sign up to set email alerts
|

Diseases and causes of death among alpacas in Sweden: a retrospective study

Abstract: BackgroundDue to increasing popularity in Sweden during the last decade, alpacas are frequently encountered by practising veterinarians and pathologists. Knowledge regarding their health and diseases under Swedish conditions is, however, limited.ObjectivesTo improve knowledge about the health of alpacas in Sweden by collecting information on diseases and health status.DesignA retrospective study was made of 93 necropsies conducted on alpacas in Sweden during the period 2001–2013.SettingData were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 5 publications
0
28
0
1
Order By: Relevance
“…Previous studies in New Zealand detected an abortion rate of 5-17% [7,8]. Other studies have shown that finding the causative agent for the abortion can be difficult, leading to a rather big proportion of cases where the reason stays unknown [9,10]. Abortion is defined as the expulsion of a fetus after organogenesis is completed and before fetal independent viability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in New Zealand detected an abortion rate of 5-17% [7,8]. Other studies have shown that finding the causative agent for the abortion can be difficult, leading to a rather big proportion of cases where the reason stays unknown [9,10]. Abortion is defined as the expulsion of a fetus after organogenesis is completed and before fetal independent viability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of these cases, 54% are reported in alpacas, 45% in llamas, and 1% in guanaco. There has been one previous summary report of causes of mortality in 100 alpacas which reported 5% rate of neoplasia (four cases of lymphoma and one case of cholangiocellular carcinoma) (2). There is one review of 40 cases of neoplasia in alpacas and llamas that found a rate of 4.9% of neoplasia in alpacas and 11% of neoplasia in llamas (3).…”
Section: Literature Casesmentioning
confidence: 99%
“…Since then, there has been increasing interest in neoplasia of llamas and alpacas especially as these animals have had increased popularity for their fiber and as companion and pack animals for integrated sheep protection. The majority of the earlier reports have been individual cases or brief communications with only very rare publications looking at overall prevalence of neoplasia in new world camelids (2,3). Prevalence studies indicate that while common, neoplasia is not a primary cause of death and that llamas might have a slightly higher incidence of neoplasia than alpacas, although alpacas appear to have predisposition for developing neoplasia at a relatively younger age.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography is especially helpful as an ancillary test in the clinical work-up of acute and chronic abdominal diseases in camelids, which are reported to be a common cause of death in llamas and alpacas [1,2]. Ultrasonographic examination of the spleen can be used to identify primary abnormalities and to differentiate strangulating obstructions, such as splenic torsion or displacement, from other causes of abdominal discomfort [3][4][5].…”
Section: Introductionmentioning
confidence: 99%